GETTING TO KNOW THE TRUE IDENTITY OF MUSLIMS THROUGH TRUE BELIEF AND GOOD MORALS - Ahmad Zaidan Salim; Muh. Ubaidillah; M. Mahbubi (International Journal of Multidisciplinary Reseach, 2025)
This study aims to explore in depth the contribution of strong faith and noble morals in shaping the identity of Muslim students in SMA Nurul Jadid Paiton Probolinggo. The formation of Islamic identity is understood as a process that does not occur instantly, but is the result of the internalization of Islamic spiritual and ethical values ​​that are continuous and sustainable. This process takes place in a conducive educational environment, which not only teaches theory, but also provides examples and real practices in everyday life. The study used a qualitative approach with a case study design, where data were collected through direct observation, in-depth interviews with key informants, and documentation of educational activities. The data obtained were then analyzed using qualitative descriptive methods to find patterns and meanings. The results of the study show that faith acts as a basic foundation that directs students' perspectives and attitudes, while morals are a real manifestation of the implementation of faith values ​​in actions and behavior. The school and Islamic boarding school environment play an important role in facilitating character formation through an integrative curriculum, value habituation activities, and consistent role models from educators. Through a dialogic and contextual educational approach, students are encouraged to understand, internalize, and practice Islamic values ​​consciously and reflectively. This finding confirms that the systematic integration of faith and morals is able to create a generation with a strong Islamic personality and ready to face the challenges of the times.